2017
DOI: 10.1038/srep42590
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin C-terminal hydrolase37 regulates Tcf7 DNA binding for the activation of Wnt signalling

Abstract: The Tcf/Lef family of transcription factors mediates the Wnt/β-catenin pathway that is involved in a wide range of biological processes, including vertebrate embryogenesis and diverse pathogenesis. Post-translational modifications, including phosphorylation, sumoylation and acetylation, are known to be important for the regulation of Tcf/Lef proteins. However, the importance of ubiquitination and ubiquitin-mediated regulatory mechanisms for Tcf/Lef activity are still unclear. Here, we newly show that ubiquitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…Uch37 has been implicated in DNA replication and cell cycle [141], TGF-β signaling [142145], WNT signaling via Tcf7 [146], longevity [147], cell migration and invasion [148], and the reversal of ubiquitination of proteasome subunits [138]. It is difficult to resolve common themes from the physiological studies reported to date.…”
Section: Physiological Functionmentioning
confidence: 99%
“…Uch37 has been implicated in DNA replication and cell cycle [141], TGF-β signaling [142145], WNT signaling via Tcf7 [146], longevity [147], cell migration and invasion [148], and the reversal of ubiquitination of proteasome subunits [138]. It is difficult to resolve common themes from the physiological studies reported to date.…”
Section: Physiological Functionmentioning
confidence: 99%
“…On the other hand, positive UCH37 expression was also reported as a prognostic marker for increased patient survival in colorectal cancer, pancreatic ductal adenocarcinoma, and gastric cancer [ 89 , 90 , 91 ]. At the molecular and cellular level, UCH37 is involved in a number of crucial signaling pathways for the regulation of cellular growth and fate, including TGF-β signaling, Wnt signaling, Hedgehog signaling, apoptosis, DNA replication/cell cycle and cell migration/invasion [ 92 , 93 , 94 , 95 , 96 ]. For example, UCH37’s binding to Smoothened (Smo) counteracts Smo ubiquitination and leads to the stabilization of the Smo protein and the activation of the Hedgehog signaling pathway [ 95 ].…”
Section: Uch37: a Cryptic And Editing Deubiquitinasementioning
confidence: 99%
“…In vitro analysis revealed that UCHL5 can inhibit migration and invasion of glioma cells mediated via a downregulation of SNRPF [142]. It was reported that UCHL5 deubiquitinates Tcf3, which helps it to fully activate the Wnt/β-catenin pathway [143]. Furthermore, the region of UCHL5 amino acid residues from 313-329 interacts with proteasomal receptor ADRM1 [144], and, according to our analysis, this ADRM1 binding region of UCHL5 is the part of disorder-based protein binding region (see Table 3).…”
Section: Intrinsic Disorder In Ubiquitin C-terminal Hydrolase Isozymementioning
confidence: 99%